Knowledge-based economy as a contemporary challenge (Economic and Political Thought, 2018)
In the changing environment, it is necessary to create conditions conduciveto the creation of entities that base their competitive advantage onknowledge. Knowledge becomes a strategic factor for the development andgrowth of competitiveness. Knowledge-based economy, the new economy,the network economy in the knowledge society are new directions for thedevelopment of the modern world. The article presents the essence, basicsand carriers of knowledge-based economy, and discusses selected definitionsof knowledge-based economy. It indicates and discusses the characteristicsof knowledge-based economy formulated by selected authors. It presents theentities that influence the creation of knowledge-based economy. It showsthat knowledge is the basic resource in an organization. The author discussesthe essence and the need for knowledge management, indicates the goals andaspects of knowledge management and presents selected factors influencingthe functioning of the knowledge management system.
Keywords: knowledge-based economy, knowledge, new economy, knowledge management